1989
DOI: 10.1007/bf00028623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photosystem II reaction center closure on nanosecond fluorescence relaxation kinetics

Abstract: The fluorescence decay of chlorophyll in spinach thylakoids was measured as a function of the degree of closure of Photosystem II reaction centers, which was set for the flowed sample by varying either the preillumination by actinic light or the exposure of the sample to the exciting pulsed laser light. Three exponential kinetic components originating in Photosystem II were fitted to the decays; a fourth component arising from Photosystem I was determined to be negligible at the emission wavelength of 685 nm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…2. Our interpretation is in line with the conclusions of Keuper and Sauer (1989). It is also supported by fluorescence decay measurements of Scenedesmus obliquus in which the middle phase increases and the fast phase decreases upon the transition from state I to state II, the latter being connected with a phosphorylation of the lightharvesting protein on the acceptor side (Wendler and Holzwarth, 1987).…”
Section: Determination O F Molecular Rate Constantssupporting
confidence: 78%
See 2 more Smart Citations
“…2. Our interpretation is in line with the conclusions of Keuper and Sauer (1989). It is also supported by fluorescence decay measurements of Scenedesmus obliquus in which the middle phase increases and the fast phase decreases upon the transition from state I to state II, the latter being connected with a phosphorylation of the lightharvesting protein on the acceptor side (Wendler and Holzwarth, 1987).…”
Section: Determination O F Molecular Rate Constantssupporting
confidence: 78%
“…This is within the limit of the values reported for the fast (200-300ps) fluorescence decay attributed to the trapping time in unfractionated thylakoids with 200-250 Chl/P-680 and in the absence of artificial acceptors (Holzwarth et al 1985, Schatz and Holzwarth 1987, Keuper and Sauer, 1989. The same trapping time was also found by an indirect measurement of the effect of DNB on fluorescence and photovoltage (Kischkoweit et al 1988).…”
Section: Trapping Kinetics and Quantum Yield In The Low Energy Limitsupporting
confidence: 70%
See 1 more Smart Citation
“…Krause, unpublished). From recent fluorescence lifetime studies (Sehatz et al 1988, Keuper and Sauer 1989, see Holzwarth 1991 it was concluded that the primary photochemical reaction is not limited by exciton transfer from the antennae to the reaction centers, but rather by the rate of primary charge separation ('trap limitation'). In such 'exciton equilibrated' systems, thermal deactivation in the antennae cannot be discriminated from that occurring in the reaction centers by means of fluorescence analysis.…”
Section: Discussionmentioning
confidence: 99%
“…8) is used; it includes: (a) trapping of the excitation energy; (b) primary charge separation, with the rate constant of forward and back reactions being influenced electrostatically by the negative charge on reduced Q A (however, only moderately; Renger et al 1995), and also by transmembrane DW and DpH (Schatz et al 1988;Meiburg et al 1983;Keuper and Sauer 1989); and (c) different energy dissipation reactions, which allow verification of the theory of Schreiber and Krieger (1996). (3) The '3-quencher' model of Steffen (2003) and Steffen et al (2001Steffen et al ( , 2005 In the model of Belyaeva and coworkers, the timedependent evolution of the fluorescence yield was calculated by multiplying the fraction of all fluorescent PSII states (hChl-P680i*) by k F /k L , where k F is the rate constant of fluorescence, and k L is the rate constant for excitation with light, which were assumed to be independent of the redox states of Q A and Q B , or the occupancy of Q B site.…”
Section: Simulation Of the Fluorescence Induction After A 10-ns Singlmentioning
confidence: 99%